Size effect-based improved antioxidant activity of selenium nanoparticles regulating Anti-PI3K-mTOR and Ras-MEK pathways for treating spinal cord injury to avoid hormone shock-induced immunosuppression - Peixin Liu; Xiaodong Liu; Zihao Wu; Kui Shen; Zhaofeng Li; Xiaowei Li; Qifeng Wu; Leung Chan; Zhong Zhang; Yutong Wu; Liwen Liu; Tianfeng Chen; et al. (Journal of Nanobiotechnology)
Abstract Spinal cord injury (SCI) is a critical condition affecting the central nervous system that often has permanent and debilitating consequences, including secondary injuries. Oxidative damage and inflammation are critical factors in secondary pathological processes. Selenium nanoparticles have demonstrated significant antioxidative and anti-inflammatory properties via a non-immunosuppressive pathway; however, their clinical application has been limited by their inadequate stability and functionality to cross the blood-spinal cord barrier (BSCB). This study proposed a synthesis method for ultra-small-diameter lentinan Se nanoparticles (LNT-UsSeNPs) with significantly superior reactive oxygen species (ROS) scavenging capabilities compared to conventional lentinan Se nanoparticles (LNT-SeNPs). These compounds effectively protected PC-12 cells from oxidative stress-induced cytotoxicity, alleviated mitochondrial dysfunction, reduced apoptosis. In vivo studies indicated that LNT-UsSeNPs efficiently penetrated the BSCB and effectively inhibited the apoptosis of spinal neurons. Ultimately, LNT-UsSeNPs directly regulated the PI3K-AKT-mTOR and Ras-Raf-MEK-ERK signaling pathways by regulating selenoproteins to achieve non-immunosuppressive anti-inflammatory therapy. Owing to their ultra-small size, LNT-UsSeNPs exhibited strong spinal barrier penetration and potent antioxidative and anti-inflammatory effects without compromising immune function. These findings suggest that LNT-UsSeNPs are promising candidates for further development in nanomedicine for the effective treatment of SCI. Graphical abstract